Pengaruh Good Corporate Governance, Leverage, Ukuran Perusahaan, Profitabilitas dan Hasil Investasi terhadap Solvabilitas (Studi Empiris pada Asuransi Jiwa Syariah yang Terdaftar di Otoritas Jasa Keuangan Periode 2018-2023) - Maulina Maalak A’rifa; Tenny Badina; Ahmad Fatoni (Universitas Muhammadiyah Surabaya, 2025)
This research aims to look at the variables of Good Corporate Governance, Leverage, Company Size, Profitability and Investment Results in influencing Solvency. The population in this study is Sharia Life Insurance companies registered with the Financial Services Authority for the 2018-2023 Period. The data used in this study is panel data from 7 selected companies, with a total sample of 42. The sampling technique uses Purposive Sampling. The analysis technique uses the panel data regression method processed using Eviews 12.0. The results of the study partially show that Company Size has a negative and significant effect on the solvency of sharia life insurance. Profitability and Investment Results have a positive and significant influence on the solvency of sharia life insurance. While the Board of Commissioners, Board of Directors, and Leverage do not affect the solvency of sharia life insurance. The results of the study simultaneously show that the variables of the Board of Commissioners, Board of Directors, Leverage, Company Size, Profitability and Investment Results have an influence on the solvency of sharia life insurance.